2011
DOI: 10.1016/j.ejcnurse.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Patterns among Jordanian Health Professionals: A Study about the Impediments to Tobacco Control in Jordan

Abstract: Effective interventions often begin with and/or depend on nurses and physicians being committed to smoking cessation. Given the very high smoking rates among nurses and physicians a key priority must be to provide quit smoking programs and to enable them to become effective champions of smoking cessation nationwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 21 publications
5
35
3
Order By: Relevance
“…Smoking habit was significantly higher among men than women. These findings are consistent with other studies on healthcare professionals and the general population in Jordan (7,15,16). These results were expected as the reported smoking prevalence rate in developing countries was also higher in men than women, and because smoking among women is not generally accepted culturally by the Jordanian population (18).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Smoking habit was significantly higher among men than women. These findings are consistent with other studies on healthcare professionals and the general population in Jordan (7,15,16). These results were expected as the reported smoking prevalence rate in developing countries was also higher in men than women, and because smoking among women is not generally accepted culturally by the Jordanian population (18).…”
Section: Discussionsupporting
confidence: 91%
“…This was lower than the prevalence rate of smoking (65%) among healthcare workers at the biggest tertiary hospital in Jordan (15), and lower than the prevalence rate of smoking (38.8%) among healthcare professionals working at other hospitals (16). This suggests that healthcare professionals at primary healthcare centres may hold a more positive attitude toward smoking habits compared to those working at hospitals.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Approximately 61% of all Jordanian households had at least one smoker (24). The data also indicated that particularly among HCPs (physicians and nurses), smoking rates were higher than the national average (39.0% overall; 46.9% among physicians and 36.1% among nurses) (25). Among youth, the Global Youth Tobacco Survey for 2009 reported rates of 11.5% and 20.7% for current cigarette and waterpipe smokers, respectively (26).…”
Section: Situation Analysismentioning
confidence: 99%
“…Jordan, a Middle Eastern country, has high prevalence rates of smoking as it ranked the fourth highest Arab country in smoking rates [5]. Some reports showed that smoking among the adult population in Jordan is estimated to be around 51% for males and 8% for females, which is unacceptably high especially for males [6].…”
Section: Introductionmentioning
confidence: 99%